PENGARUH DAYA TARIK WISATA DAN FASILITAS REKREASI TERHADAP KEPUTUSAN BERKUNJUNG KE SITU BAGENDIT - Putri Wafda Fauziah; Fitria Rahmafitria; Rosita, Rosita (Media Bina Ilmiah, 2025)
One of the key factors for tourists in choosing a destination is its attractions, both natural and recreational facilities. The general concept suggests that natural attractions and recreational facilities positively influence the decision to visit. This study aims to analyze the impact of these two factors on tourists’ decisions at Situ Bagendit and compare the magnitude of their influence. The revitalization of Situ Bagendit has increased visitor numbers, but many tourists still feel dissatisfied. This research employs a quantitative method with SEM PLS analysis using the Smart PLS 3 application, involving 100 respondents who visited Situ Bagendit between 2018-2023, selected using the Slovin formula and online questionnaires. The results show that natural attractions influence visiting decisions by 68.2%, while recreational facilities account for 23.5%. Thus, natural attractions have a greater impact than recreational facilities on tourists’ decisions to visit Situ Bagendit.